Alienasi, Self Disclosure ANALISIS KETERAMPILAN SELF DISCLOSURE PADA REMAJA PANTI ASUHAN YANG MENGALAMI ALIENASI DI PANTI ASUHAN AISYIYAH HIKMAH ZAM-ZAM BANJARMASIN - Sarnadilah, Mayadah; Maimanah; Faridah, Siti (Faculty of Ushuluddin and Humanities, 2025)
Alienation is a condition in which individuals feel isolated from their social environment. Adolescents, particularly those living in orphanages, are more vulnerable to this experience. This study aims to explore the self-disclosure skills of adolescents at Orphanage who experience alienation. Using a qualitative descriptive method, data were collected through observations and in-depth interviews with the adolescents and caregivers. The findings reveal that self-disclosure skills among these adolescents include aspects such as accuracy, motivation, timing, intensity, depth, and breadth. They are more likely to share personal stories with peers or older siblings rather than with caregivers. Several factors contribute to their sense of alienation, including negative first impressions, perceived injustice, differences in behavior, physical appearance, difficult personality traits, economic conditions, and residential background. Notably, adolescents with traumatic experiences tend to withdraw more due to negative early interactions within the social environment.